The deteriorating jurisdiction of indigenous people's courts in the US and in the Philippines - Salud, Jan Raphael R. (Animo Repository, 2019)
All Indigenous Peoples have one thing in common they all share a history of injustice. They have been killed, tortured and enslaved, and have been denied the right to participate in govemment." Conquest and colonization have attempted to steal their dignity and identity as indigenous peoples, as well as their fundamental right of self-determination.To heal these injustices, many countries have introduced laws to integrate indigenous peoples into their political and govermmental structures. Some of these laws involve the creation and recognition of indigenous people's courts. Sadly, recent jurisprudential developments in the Philippines and in the United States tend to weaken, rather than strengthen, these courts. This paper attempts to study the history, the structure and the recent developments involving indigenous people's courts in the Philippines and in the United States, and explore how their jurisdiction has diminished throughout the years.